Al[18F]NOTA-T140 Peptide for Noninvasive Visualization of CXCR4 Expression. - Yan, Xuefeng; Niu, Gang; Wang, Zhe; Yang, Xiangyu; Kiesewetter, Dale; Jacobson, Orit; Shen, Baozhong; Chen, Xiaoyuan; Kiesewetter, Dale O (Molecular Imaging & Biology, 2016)
Purpose: Chemokine receptor CXCR4 plays an important role in tumor aggressiveness, invasiveness, and metastasis formation. Quantification of CXCR4 expression by tumors may have an impact on prediction and evaluation of tumor response to therapies. In this study, we developed a robust and straightforward F-18 labeling route of T140, a CXCR4 peptide-based antagonist.Procedures: T140 derivative was conjugated to 1,4,7-triazacyclononane-triacetic acid (NOTA) and labeled with Al[(18)F]. Al[(18)F]NOTA-T140 was evaluated in vitro in cell-based assay and stability in mouse serum and in vivo using CXCR4 positive and negative tumor xenograft models.Results: Labeling of Al[(18)F]NOTA-T140 was completed within 30 min with a radiochemical yield of 58 ± 5.3 % at the end of synthesis, based on fluoride-18 activity. Al[(18)F]NOTA-T140 accumulated in CHO-CXCR4 positive but not negative tumors. Al[(18)F]NOTA-T140 uptake in the tumors correlated with CXCR4 protein expression. Moreover, Al[(18)F]NOTA-T140 had high accumulation in CXCR4-positive metastatic tumors.Conclusions: The simplicity of Al[(18)F]NOTA-T140 labeling along with its properties to specifically image CXCR4 expression by tumors warrant further clinical application for the diagnosis of CXCR4 clinically.